Survival Impact of Initial Therapy in Patients with T1-T2 Glottic Squamous Cell Carcinoma. (August 2016) - Brady, Jacob S.; Marchiano, Emily; Kam, David; Baredes, Soly; Eloy, Jean Anderson; Park, Richard Chan Woo
Objective: Laryngeal cancer most commonly arises from the glottis. Comparable outcomes in survival have been shown in patients with early glottic squamous cell carcinoma treated with either surgery or radiotherapy. Study Design and Setting: Administrative database study. Subjects and Methods: The US National Cancer Institute's SEER database (Surveillance, Epidemiology, and End Results) was queried for cases of early glottic cancer (T1-T2N0M0, 1988-2012). We identified 13, 312 qualifying cases. Patient demographics, therapeutic measures, and survival outcomes were examined with appropriate univariate and multivariate analyses. Results: Early glottic cancer has a mean age at diagnosis of 64.8 ± 11.6 years and a male:female ratio of 6.9:1. The most common treatment modality was radiotherapy alone (51.6%), followed by combination therapy with surgery first (31.5%). Overall, the 5-year disease-specific survival (DSS) rate was 88.4%. When stratified by treatment modality and stage, 5-year DSS for T1 tumors was 93.2% with surgery alone and 89.0% with radiation alone ( P < .0001). With combination therapy, the 5-year DSS was 91.3% for surgery first and 84.9% for radiation first ( P = .0239). In T2 tumors, 5-year DSS was improved with single-modality therapy versus multimodality therapy (81.1% vs 76.4; P = .0255). Conclusion: In T1 disease, surgery alone shows improved 5-year DSS versus radiation alone, but this difference was not observed in T2 tumors. Additionally, surgery, rather than radiation, shows improved 5-year DSS when implemented as a first-line therapy. Combination therapy does not show improved 5-year DSS for early glottic cancer.